Radiotherapy in selected non-oncological neurological disorders – efficacy and safety - Kulig, Klaudia; Wiśniowski, Maksymilian; Redner, Aneta; Popiel, Michal; Dziekoński, Kamil; Zwierzchlewska, Patrycja; Buczek, Kacper; Smala, Kamila; Stanibuła, Dominik; Wiśniowska, Ada (Quality in Sport, 2025)
Introduction: Radiotherapy, once limited to oncology, is now emerging as a therapeutic option for non-neoplastic neurological disorders. Advances in stereotactic techniques such as Gamma Knife and CyberKnife allow for precise functional targeting, opening possibilities in diseases like Alzheimer’s disease (AD), drug-resistant epilepsy, and trigeminal neuralgia (TN). Materials and Methods: A comprehensive literature review was conducted using PubMed, Scopus, and ClinicalTrials.gov. Search terms included radiotherapy, stereotactic radiosurgery, Alzheimer’s disease, epilepsy, and trigeminal neuralgia. Studies published between 2015–2025 were reviewed. Results: In AD, low-dose radiation therapy (LDRT) has shown potential to stabilize or improve cognition, with minimal side effects in early clinical trials. In epilepsy, stereotactic radiosurgery (SRS) and fractionated stereotactic radiotherapy (FSRT) have provided seizure reduction or remission in selected cases, particularly where surgery is not viable. For TN, SRS achieves pain relief in 85–90% of patients, with long-term remission and generally mild adverse effects such as facial numbness. Conclusions: Radiotherapy offers a promising, non-invasive approach for selected neurological conditions. Although current data are encouraging, larger randomized trials are essential to establish long-term safety, optimize dosing strategies, and validate efficacy across patient populations.